Peran Dakwah Ekonomi Syariah dalam Pemberantasan Riba (Studi Kasus Bank Muamalat Indonesia) - Ahmad Luthfi (Jurnal Syntax Transformation, 2023)
Bank Muamalat is a pioneer of Islamic banking. With the existence of Bank Muamalat, other Islamic banks are now mushrooming. Besides that, Islamic banks promise to create economic stability. Islamic banks are one of the avengers of punishment from Allah SWT for perpetrators of usury eating, and Islamic banks always invite people to stay away from eating usury. So avoid punishment. Bank Muamalat always tries to be at the forefront of eradicating usury through its sharia banking. Bank Muamalat facilitates office space by building places of worship, such as small prayer rooms whose capacity is used according to the number of employees. Ordaining Islamic law not only limited to the problem of restricting usury, but it will always try to also adhere to other Islamic teachings, such as inviting employees to pray in the congregation when they are in the office, as well as temporarily closing office activities during prayer hours, such as at midday and midday prayers. The impact of Da'wah in the field of Islamic Economics at Bank Muamalat can be felt today. With the Islamic economic approach as a medium of da'wah run by Bank Muamalat as a pioneer in Indonesia, we can see the spread of the Islamic system in various bank and non-bank financial institutions so that people can choose a service model. the services needed, whether banking, leasing, insurance, cooperatives, all exist with operational principles and sharia services. Indicators of the role of Islamic economic da'wah in eradicating usury with the rise of bank and non-bank financial institutions, businesses, and sharia markets show that the influence of the sharia system has developed and grown widely in the people of the nation and state of Indonesia, so that it can be interpreted as the contribution of da'wah in eradicating usury has provided benefits to the Muslim community in particular, and the Indonesian people in general. The contribution of the Islamic economy in eradicating usury by being the oldest bank that carries sharia principles, bank Muamalat has set an example for the Indonesian nation, how an Islamic financial institution whose work was doubtful at first, can survive decades and continue to grow to this day. To build an economy and finance based on Islamic religious law.